Strategies for realizing a superior school at Muhammadiyah Nurul 'ilmi Elementary School Karangdowo, Klaten - Indriasari, Pipit Saraswati; Narimo, Sabar; Fuadi, Djalal (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan UIN Raden Fatah, 2024)
Excellent schools are schools that are in great demand by parents, to make this happen, a good strategy is needed. The principal at SD Muhammadiyah Nurul 'Ilmi created a superior program to attract parents' interest. The aim of this research is to describe the strategies implemented by school principals in creating superior schools at the Muhammadiyah Nurul 'Ilmi Elementary School, Karangdowo , Klaten . This research uses a qualitative approach to reveal events with a thorough explanation of what they are. The research design used is ethnography. Ethnographic research is a genre of qualitative research, developed from anthropological methodology. The research was conducted at Muhammadiyah Nurul 'ilmi Elementary School with the research subject being the school principal. The validity of the data in this research uses triangulation. The principal's strategy in creating a superior school at the Muhammadiyah Nurul 'ilmi Elementary School, Karangdowo , Klaten includes: Developing a school plan to the maximum, analyzing the obstacles, challenges and future opportunities that will be faced. Increasing the effectiveness of learning, by supervising the school principal and implementing appropriate learning strategies and methods. Improving the quality of teachers by participating in KKG, seminars and continuing education to the next level. Improvement Program in the Field of Student Development, through extracurricular activities that facilitate students' talents and interests. Establish relationships with parents, stakeholders and the surrounding community to increase cooperation and foster good relationships.